Proceedings of the 3rd International Conference on Learning Innovation and Quality Education (ICLIQE 2019) 2020
DOI: 10.2991/assehr.k.200129.052
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Use of Digital-Based Educational Comic Media in Improving Reading Interest in Elementary School Students

Abstract: This research aimed to obtain information about the effectiveness of digitalbased educational comic media in improving reading interest of elementary school students This research is a the experimental research with design the one group pretest posttest. The research subjects were the students of SDN Jogorogo 3 and SDN Talang, Ngawi Regency in the 2018/2019 academic year. The data collection techniques using questionnaires and data analysis techniques using t-test. This research discusses the increase in readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
(6 reference statements)
1
7
0
1
Order By: Relevance
“…The score of the t-table is higher than the score t-table.This research has demonstrated the effectiveness of inserting learning media to improve reading comprehension. This study, in line with previous evidence(Surya et al, 2020), explained that using media, specifically digital-based educational comics, effectively improved reading interest in elementary school students. Applying digital-based educational comic media in learning can improve students' reading interest.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The score of the t-table is higher than the score t-table.This research has demonstrated the effectiveness of inserting learning media to improve reading comprehension. This study, in line with previous evidence(Surya et al, 2020), explained that using media, specifically digital-based educational comics, effectively improved reading interest in elementary school students. Applying digital-based educational comic media in learning can improve students' reading interest.…”
supporting
confidence: 90%
“…Then, the t- (Surya, Poerwanti, and Sriyanto 2020). This research finding was contrary to (Topal et al, 2019) mention that media is ineffective in teaching reading.…”
Section: Hypothesis Testingmentioning
confidence: 62%
“…Comics and picture story books are examples of visual media that can be used to overcome student boredom in reading. One of the learning media that can be used to overcome the low reading interest of students is by presenting digital-based educational comic media according to the characteristics of students (Surya et al, 2020). Saputro & Soeharto (2015) in their research that developed character-based comic media in the thematic integrative learning for fourth grade elementary school which concluded that learning with comics media was effective in increasing students' character values.…”
Section: Figure 1 Diagram Of Students' Daily Reading Intensitymentioning
confidence: 99%
“…Efforts to grow students' reading interest and reading skills have been programmed by the government by launching the School Literacy Movement program, which is the ability to access, understand, and use smart things through various activities, including reading, viewing, listening, writing or speaking (Surya et al, 2020). However, the role of the government alone is not enough.…”
Section: Introductionmentioning
confidence: 99%
“…Membaca komik dapat menumbuhkan sikap kritis pada anak, menstimulus minat membaca, dan memberikan arahan pada siswa yang tidak suka membaca agar disiplin untuk membaca (Rosyida, Mustaji, & Subroto, 2018). Definisi literasi adalah kemampuan untuk mendapatkan informasi secara tertulis meliputi tahap keterampilan memahami, mengimplementasikan, dan melakukan refleksi terhadap informasi bacaan sesuai dengan tujuan dalam membacanya (Surya, Poerwanti, & Sriyanto, 2020). Nurjannah, Wahyudi, & Setiawan (2018) memberikan penguatan bahwa memanfaatkan komik sebagai media pembelajaran merupakan pilihan yang tepat bertujuan meningkatkan literasi pada siswa.…”
Section: Pendahuluanunclassified